Adaptive protection for voltage instability mitigation scenario - Abidin I.Z.; Ahmad N.; Zahidi R.A.; Hashim H.; Hussein Z.F.; Omar Y.R.; Hashim A.H. (2023)
Modern power system network are usually operated to its maximum capabilities. This in turn would expose the system towards possible voltage instability condition. Coupled with peak load condition where lines can be loaded to its limit, probable scenarios relating to voltage instability could lead to tripping of overload lines which would then lead to possible cascading tripping; ultimately lead towards voltage collapse condition. However, possible mitigating action is possible which could reduce the line loading and ultimately push the system back towards a voltage stable condition. This paper demonstrates a possibility of this occurring utilizing Fast Voltage Stability Index (FVSI) approaches to quickly assess the network voltage stability. Results show that these mitigating action does improve the stability of the system hence lead to a possible Wide Area Protection application which is synonymously linked to a smart grid system. 2009 IEEE.